11
Look at the series:
2 & 6 +4
6 & 3 -3
3 & 8 +5
8 & 6 -2
6 & 12 +6
See the pattern that develops you switch between adding & subtracting. The additions increase by one each time & the subtractions decrease by 1. So following the pattern, the next number 12 subtracted by 1, since subtraction is the next operation in the series & the previous subtraction was by 2, so the next one will be by 1. Hence, 12 -1 = 11
Chat with our AI personalities
The number is 12. 12 ÷ 2 = 6 6 - 4 = 2
It is a deficient number. The first abundant number is 12. 12: 1,2,3,4,6,12 which equal 28 28>(12*2) and the abundance is 28-(12*2)=4
2*2*3 = 12
27. But that continues the sequence, it does not complete it.
2/3 of 12 = 12*2/3 = 8